2011
DOI: 10.1002/app.34591
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the transition temperature at different cooling rates and its influence on prediction of shrinkage and warpage in injection molding simulation

Abstract: In injection molding simulation the phase change from melt to solid state is usually simplified by using a so called transition temperature. In the present work, the transition temperatures of several amorphous and semicrystalline polymers were determined using DSCruns at different cooling rates. The transition temperature was described as a function of cooling rate. The obtained transition temperatures of the semicrystalline polymers were used in injection molding simulations with the commercial software pack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…The boundary conditions of the manufacturing process, such as injection speed and holding time, have been considered in the simulation. Although the geometry is quite simple, the prediction of the warpage shows a significant difference to the measurement (see figure 3 These results are in agreement to the results of other groups such as [1] and [8]. This is an indicator, that the assumption of homogenous material properties is already violated for a simple box geometry.…”
Section: Pixels X [-]supporting
confidence: 88%
“…The boundary conditions of the manufacturing process, such as injection speed and holding time, have been considered in the simulation. Although the geometry is quite simple, the prediction of the warpage shows a significant difference to the measurement (see figure 3 These results are in agreement to the results of other groups such as [1] and [8]. This is an indicator, that the assumption of homogenous material properties is already violated for a simple box geometry.…”
Section: Pixels X [-]supporting
confidence: 88%
“…Altan and Yurci [34] found that the mold temperature is the most important parameter for residual stresses on the surface layer of injection-molded HDPE articles, which was also reported by Wang and Young [26] . In our recent studies [17, 35 -39] , the cooling stage of IM was numerically investigated using the enthalpy transformation methodology (ETM) [10,40] , which is a useful way to handle the multidimensional phase-change issues [39,41] . Our findings suggested that the mold temperature exerts more significant influence on the cooling rate compared with the melt temperature [35,42] .…”
Section: Introductionmentioning
confidence: 99%
“…[12] Due to the complexity of the phase change especially when considering semi crystalline polymers, this simple approach is still state of the art in commercial software. [21][22][23] Lucyshyn et al [24] investigated the influence of the cooling rate on the transition temperature. He found, that a higher cooling rate causes a decrease in transition temperature for semi crystalline materials while no significant change was observed for amorphous materials.…”
Section: Materials Datamentioning
confidence: 99%